A Juridical-Historical Review of the Formation of Halal Product Assurance Regulations in Indonesia - Gilalo, Jacobus Jopie; Waspada; Rumatiga, Hidayat; Erbiana, Nyi Mas Gianti Bingah (DE'RECHTSSTAAT, 2025)
Before the enactment of Law Number 33 of 2024 concerning Halal Product Assurance (Halal Product Assurance Law/HPAL), various regulations governing halal requirements had already been in force. However, those regulations were still partial and not integrated into a comprehensive system capable of providing legal certainty. Therefore, it is important to examine the background of the establishment of the HPAL in order to fully understand the legislative process behind it. Through a normative juridical study with a historical approach, the foundation for the formation of the HPAL can be described. The findings indicate that the enactment of the HPAL provides legal certainty and protection for Muslims in Indonesia in using and consuming products in accordance with Islamic law, namely those that are permissible (halal) and avoiding those that are prohibited (haram). This law also serves as a significant milestone in raising public and business awareness regarding the importance of halal certification as both a guarantee of quality and a reflection of Islamic identity. Furthermore, the presence of the HPAL is expected to harmonize regulations among the government, certification bodies, and business actors. Thus, the implementation of halal regulations can proceed more effectively, systematically, and consistently. Ultimately, the HPAL not only functions as a legal instrument but also as a means of protecting the rights of Muslim consumers while strengthening the competitiveness of Indonesian halal products in the global market.